Peran Orang Tua Dalam Self-Control Remaja Punk: Studi Kasus Komunitas Punk Di Kecamatan Sarang, Kabupaten Rembang - Shifatul Khasanah; Alfi Zumruda; Abdul Najib (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2020)
This research studies how important a parent's role to construct SelfControl of an adolescence punk. Design of this research applied qualitative approach where data collection use observation, interview, and documentation techniques at the site from three categories respondents included punk member, former of punk, and ex-punk that live around punk lives environment. The researchers analyze the data with Stephen R. Covey's theory human determinism which is say that human have three attitude source and that is genetic, psychic, and environment. The results show that parent role is important to construct teenager's Self-Control, demonstrably with (1) adolescences punk were allowed by their parrent to join Punk and even followed their parrent as member of Punk (2) adolescence punk were lost directions because of the conditions of their family. (3) adolescence who lived around Punk circle but they don' join Punk because they have proper control form their parrents. So, once again, the role of parents is very important to adolescence because as we know from data, member of punk have "under control" self-control which means that their acts were free with no rule.